Correlation of Hypocalcemia with eGFR in Chronic Kidney Disease: A Cross Sectional Study in Marine City Medical College and Hospital (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Chronic Kidney Disease (CKD) poses a significant global health challenge. Its ramifications include advancing to End-Stage Renal Disease (ESRD) developing various complications stemming from compromised kidney function, and heightened vulnerability to Cardiovascular Disease (CVD). Interestingly, even within the bounds of normalcy, lower serum Calcium (Ca) levels emerge as a risk factor for precipitating a swift decline in estimated Glomerular Filtration Rate (eGFR) in CKD. Through extensive multivariable correlation analyses, it's been unveiled that serum calcium levels exhibit a correlation with eGFR. The current study aims at elucidating a link between serum calcium levels and eGFR among CKD patients. Materials and methods: A cross-sectional study was conducted from January 2023 to December 2023, by the Department of Biochemistry in conjunction with the Department of Nephrology at Marine City Medical College & Hospital (MCMCH). Purposive sampling was employed to recruit a total of 224 subjects of 18 years and above, after following the inclusion criteria and obtaining permission from ethical/institutional review board (IRB). The study population was grouped as CKD: stage III (eGFR 30-59 ml/min/1.73m²) stage IV (eGFR 15-29 ml/min/1.73m²) and stage V (eGFR